Multimedia Interaktif Pengenalan Nama Buah Dalam Bahasa Inggris Untuk Anak Usia Dini - Monikha Oktra Bella; Arif Prambayun; Putri Maharani (Universitas Multi Data Palembang, 2022)
Abstract: This interactive multimedia design aims to help educators, especially in kindergarten schools, in understanding the world, especially to recognize fruit names in English. This interactive multimedia will be equipped with Indonesian sounds so that early children are able to remember the names and shapes of fruits, usually in kindergarten schools, educators guide students to learn to recognize fruit names in English using props. This of course makes it difficult for students to name fruit in English with good and correct spelling. This interactive multimedia design uses the concept of learning while playing, resulting in an interactive multimedia design that can be usedfor early childhood as a learning medium with the guidance of educators or parents. Abstrak: Perancangan multimedia interaktif ini bertujuan untuk membantu para tenaga pendidik khususnya di sekolah taman kanak-kanak dalam memahami dunia, terutama untuk mengenal nama buah dalam bahasa inggris. Multimedia initeraktif ini akan dilengkapi dengan sound bahasa Indonesia agar anak usia dini mampu mengingat nama dan bentuk buah, biasanya di sekolah taman kanak-kanak tenaga pendidik membimbing peserta didik untuk belajar mengenal nama buah dalam bahasa inggris menggunakan alat peraga. Hal ini tentunya menyulittkan bagi peserta didik dalam menyebutkan nama buah dalam bahasa inggris dengan ejaan yang baik dan benar. Perancangan multimedia interaktif ini menggunkan konsep belajar sambil bermain, sehingga menghasilkan perancangan multimedia interaktif yang dapat digunakan untuk anak usia dini sebagai media pembelajaran dengan bimbingan tenaga pendidik atau orangtua.